Emotional Intelligence and Academic Adjustment Among Kuwaiti University Students - Dr. Halima Ibrahim Al-Failakawi; ALDABOUS, Dr. RANA SFJ; ALENZI, FAISAL K HS.; AL ALRASHEDI, FAHAD M KH. (Journal of Posthumanism, 2025)
This study investigates the role of emotional intelligence (EI) in academic adjustment among university students in Kuwait. Using a stratified random sample of 400 undergraduate students (200 males, 200 females) from various academic years and majors, the research employed validated self-report measures to assess EI and academic adjustment. The results revealed a significant positive correlation between emotional intelligence and academic adjustment (r = 0.62, p < 0.01), suggesting that students with higher EI are better equipped to handle academic challenges. Gender differences were found in EI (favoring females), but not in academic adjustment. Emotional intelligence increased significantly across academic years, while no significant differences were observed between scientific and literary majors. These findings highlight the importance of EI in facilitating students’ adaptation to university life. The study recommends implementing EI-based support programs to enhance students’ academic and personal development.